The Use of Image Media in Arabic Language Lessons to Improve the Ability to Memorize Mufradat in Grade VII Students of MTs Sirnamiskin - Abdul Kodir; Ahmad Fawaiz Hakim (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the effectiveness of using picture media in Arabic language instruction to enhance vocabulary (mufradat) memorization skills among seventh-grade students at MTs Sirnamiskin. The research employs a pre-experimental design with a one-group pre-test and post-test model. A total of 31 students participated as the research sample, comprising 22 males and 9 females, selected through purposive sampling. Data were collected using vocabulary memorization tests administered before and after the intervention, as well as through observation and documentation. The learning intervention involved integrating picture media into Arabic lessons across two cycles, focusing on the planning, implementation, observation, and reflection stages. The findings indicate a notable improvement in students' vocabulary memorization abilities, with the average pre-test score increasing from 60 in the first cycle to 70 in the second cycle, and the post-test scores rising to 75 and 85, respectively. Students showed higher engagement and retention when vocabulary was introduced through relevant and visually appealing images. The observations further confirmed increased participation and enthusiasm during lessons using picture media. In conclusion, the use of picture media proves to be an effective instructional strategy in Arabic language learning, particularly for enhancing students’ ability to memorize mufradat. It is recommended that Arabic language teachers incorporate picture media into their teaching practices to support more engaging and meaningful learning experiences at the secondary school level.